Adiponectin, total anti-oxidant status, and high sensitivity C-reactive protein in Indonesian men with metabolic syndrome (Faculty of Medicine Universitas Indonesia, 2009)
Aim To examine biochemical markers of adiponectin, total anti-oxidant status (TAOS) and high sensitvity C-reactive protein (hsCRP) in individuals with and without metabolic syndrome (MetS). Methods A cross-sectional study on 36 non-MetS and 36 MetS subjects was undertaken in Jakarta. Measured indicators were adiponectin, TAOS and hsCRP, apart from weight, height, waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), and fasting blood glucose (FBG). Odds ratio (OR) of adiponectin, TAOS and hsCRP were calculated to assess risk for the development of MetS. Median values were determined as cut-offs to define high and low values of each parameter. Relationships between adiponectin, TAOS and hsCRP with WC were analyzed by using Spearman correlation analysis, and the contributions of all indicators to the development of MetS were analyzed by using logistic regression. Results: Adiponectin dan hsCRP differed significantly between non MetS and MetS subjects (4.2 + 1.4 vs 3.1 + 1.0 ug/mL) dan (0.97 + 0.92 vs 3.35 + 3.43 mg/L) (p < 0.01), but no significant difference was found in TAOS (1.24 + 0.1 vs 1.28 + 0.2 mmol/L). Adiponectin associated negatively with WC (rs= -0.436; p < 0.01), while TAOS and hsCRP associated positively with WC (rs= 0.286, p = 0.02 and rs= 0.597, p < 0.01). The odds ratios (ORs) of adiponectin and hsCRP for the development of MetS were 4 (p = 0.01) and 6,8 (p < 0.01), respectively; while the risk of subjects with adiponectin-hsCRP ratio of ≤ 2.31 to develop MetS was 25 times (p < 0.01) those with adiponectin-hsCRP ratio > 2.31. Conclusion The use of adiponectin-hsCRP ratio increases the predictive power for the occurrence of MetS by 4-6 times the predictive power of adiponectin or hsCRP alone. (Med J Indones 2009; 18: 262-8)